EFFECTS EMPLOYEE’S ETHIC ON ORGANIZATIONAL PERFORMANCE - MyoHtike, Zin (International Journal of Psychosocial Rehabilitation, 2020)
Ethics demonstration to employees treating as equal opportunities and negotiating are make management process between ethically responsible in integrity of business of laws, fairly, honestly and open minded across the management between team and customers relation in operation.The research measured what progress ofemployee’s ethic hadbeen practice actually in the organization, this study found that the effects ethic of employeesand organizational performance effectiveness. Managing the business operatedasethical standards in all clients, customers, suppliers, environment and the communities are able to take into action by the employees. Organization showed to prove an efficient, effectively protectedfrom unethical doing can be increased in performance in return high flow in revenues of organization.Effective ethical leaders for decision making as commitment, credibility implemented the highest and strongly demonstrate respect service within the organization by the effort of coaching, mentoring and training to develop performance